Assessment of residents' neighbourhood confidence in an African traditional city: The Abeokuta experience - Oluwaseun Olowoporoku; Adetayo Salami; Olamide Akintifonbo (Economic and Environmental Studies (E&ES), 2017)
This study examined the socio-economic attributes of respondents, their level of satisfaction with available infrastructure and services and intra-urban variation in residents level of neighbourhood confidence in Abeokuta Nigeria. The stratified residential zones are the older residential areas, newer residential areas and the Government Reserved Areas (GRA). A total of 123 residents were selected for survey using systematically sampling technique. The study revealed that residents' socio-economic attributes such as income and educational status varied significantly with different residential areas. Findings revealed that there is low level of satisfaction with available facilities and services as they rated 2.9, 2.9 and 3.4 in the older, newer and GRA residential areas. Similarly, the mean neighbourhood confidence indices for the older residential area, newer residential area and GRA were 3.3, 2.9 and 3.7 respectively. The most important factor that increased residents' confidence in the newer residential area and GRA was conducive physical environment for child raising with indices 3.6 and 4.2 respectively, while the most important factor that increased residents' confidence in the older residential area was social cohesion. It recommended government provision of environmental amenities across the residential areas as well as encouragement of home ownership through the provision of housing schemes at low prices and interest rate.
Keywords: O1; O18; 330; neighbourhood; confidence; residential area; GRA; facilities; services; Abeokuta